Trends in the epidemiology of childhood nephrotic syndrome in Africa: A systematic review (2021)
Background: Childhood nephrotic syndrome, if left untreated, leads to progressive kidney disease or death. We quantified the prevalence of steroid-sensitive nephrotic syndrome, steroid-resistant nephrotic syndrome, and histological types as the epidemiology of nephrotic syndrome in Africa remains unknown, yet impacts outcomes. Methods: We searched MEDLINE, Embase, African Journals Online, and WHO Global Health Library for articles in any language reporting on childhood nephrotic syndrome in Africa from January 1, 1946 to July 1, 2020. Primary outcomes included steroid response, biopsy defined minimal change disease, and focal segmental glomerulosclerosis (FSGS) by both pooled and individual proportions across regions and overall. Findings: There were 81 papers from 17 countries included. Majority of 8131 children were steroid-sensitive (64% [95% CI: 63–66%]) and the remaining were steroid-resistant (34% [95% CI: 33–35%]). Of children biopsied, pathological findings were 38% [95% CI: 36–40%] minimal change, 24% [95% CI: 22–25%] FSGS, and 38% [95% CI: 36–40%] secondary causes of nephrotic syndrome. Interpretation: Few African countries reported on the prevalence of childhood nephrotic syndrome. Steroid-sensitive disease is more common than steroid-resistant disease although prevalence of steroid-resistant nephrotic syndrome is higher than reported globally. Pathology findings suggest minimal change and secondary causes are common. Scarcity of data in Africa prevents appropriate healthcare resource allocation to diagnose and treat this treatable childhood kidney disease to prevent poor health outcomes. Funding: Funding was provided by the Canadian Institute for Health Research (CIHR) and the National Institute of Health (NIH) for the H3 Africa Kidney Disease Research Network. This research was undertaken, in part, from the Canada Research Chairs program.